MODEL PENCATATAN AKUNTANSI DI BADAN USAHA MILIK KAMPUS UNIVERSITAS MUHAMMADIYAH GORONTALO - Radjak, Lukfiah Irwan; Hiola, Yustina (JSAP : Journal Syariah and Accounting Public, 2022)
This study aims to develop a design model for accounting records in Business Entities Owned by the University of Muhammadiyah Gorontalo. The targeted output of this research is the design of a simple recording model on the University of Muhammadiyah Gorontalo Campus-Owned Enterprises and the research results can be published in local and national journals that have ISSN. This research is a qualitative research with data collection methods through observation, interviews and documentation. This research will lead to the design of an accounting record model that can be used by the University of Muhammadiyah Gorontalo Campus-Owned Enterprises in accordance with SAK EMKM which is based on the needs of routine and non-routine transactions on the entity. The results of this study indicate that BUMK UMGo is not ready to prepare its financial statements independently. Financial recording is still on a cash basis, there is no going concern analysis and has not applied the concept of a business entity. BUMK UMGo does not yet have adequate accounts receivable subsidiary ledger records, inadequate inventory records and the absence of accounting policies. BUMK UMGo is starting to be able to fix its accounting records starting by complying with the basic accounting assumptions required in SAK EMKM, namely recording transactions on an accrual basis, having going concern analysis and applying the concept of business entities. In addition, pay attention to the transaction subsidiary books, which so far have only been cash books as a control over all accounts that cannot accommodate accrual transactions.